Problem Solving Profile of Class IX Junior High School Students Viewed from Spatial Visual Intelligence on Building Materials Room - Salim, Affandi Amat; Jaeng, Maxinus; Yadil, M. Nur (Jurnal Riset Pendidikan MIPA, 2018)
The purpose of this study was to obtain a description of the problem-solving grade IX SMP Labschool UNTAD Palu in problem-solving solid figures in terms of visual-spatial intelligence. This study used a qualitative method that is based on the problem-solving steps proposed by Polya. The results showed at the stage of understanding the problem (1) student of high visual-spatial intelligence was drawn objects contained in the problem and make an example at the points in the image according to their own understanding to identify the information contained in the problem. As well as these students can mention all the information that exists correctly. (2) student of mid visual spatial intelligence was to draw objects in the problem to identify information contained in the problem. As well as these students can mention all the information that exists correctly. (3) student of low visual spatial intelligence can mention all the information that exists correctly. At the stage of making a plan (1) student of high visual spatial intelligence prefer shorter and less common strategies to solve problems, namely to find the area of all upright sides in the pyramid and add to the area of the beam without a roof. (2) student of mid visual spatial intelligence are choosing a very common strategy for solving problems, namely looking for the surface area of the beam, adding it to the surface area of the pyramid. Then the sum of results will be reduced by the area of the base of the pyramid and the area of the roof of the beam. (3) student of low visual spatial intelligence experience difficulties and are incomplete in determining problem solving strategies. At the stage of carrying out the plan (1) student of visual spatial intelligence can implement strategies to solve problems correctly. (2) student of mid visual spatial intelligence are able to apply strategies to solve problems correctly. (3) student of low visual spatial intelligence experience difficulties when working on problems and cannot solve problems correctly. At the stage of looking back (1) student of high visual spatial intelligence is very thorough in re-examining the work step by step and reexamining the results that have been obtained. Student believe the truth of the answer by recalculating and concluding the results obtained correctly. (2) student of mid visual spatial intelligence is not re-examining the results that have been obtained because they have believed the truth of the answer. (3) student of low visual spatial intelligence do not re-examine the results that have been obtained because of doubt.